A Comprehensive Review of Counterfeit Luxury Brands Scenario in India: The Impact of Counterfeit Luxury Brands on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Counterfeiting is affecting the global economy at a very serious level. Counterfeit products affect the employment as medium and small industries are heavily affected, destroy the market of original products, and degrade the goodwill of the concerned industries. As a whole, it is a loss to an economy. Right from FMCG to Jewellery, handbags to shoes, electric cords to television, counterfeits leave no sector untouched. This paper uses secondary data approach. The result of this study reveals that authentic luxury brands associated with high reputation and prestige are often susceptible to counterfeiting. The authentic luxuries branded products are closely associated with high price. These research outcomes support the theory of luxury brand associations.